2022
DOI: 10.1109/trpms.2022.3158704
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study on the Timing Limits of the TOFPET2 ASIC and on Approaches for Improvements

Abstract: Novel electronic readout schemes of analog SiPMs have shown impressive timing performance of γ-detectors in positron emission tomography (PET). However, transfering these novel concepts to system level is key to exploit the improved coincidence time resolution (CTR) in (pre-)clinical imaging. In this study, the commercially available TOFPET2 ASIC from PETsys Electronics S.A. is tested in terms of the best achievable CTR. The measurable CTR limits will be obtained by state-of-the-art high-frequency (HF) readout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
3
17
0
Order By: Relevance
“…6b). The measurement of the LYSO:Ce:Ca reference detector has an optimal CTR of (68 ± 1) ps similar to measurements presented in [32]. Measuring two 2 × 2 × 20 mm 3 BaF 2 crystals in coincidence shows a distinguishable Compton edge and photopeak, but the peak separation is significantly reduced for these longer crystals (see Fig.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…6b). The measurement of the LYSO:Ce:Ca reference detector has an optimal CTR of (68 ± 1) ps similar to measurements presented in [32]. Measuring two 2 × 2 × 20 mm 3 BaF 2 crystals in coincidence shows a distinguishable Compton edge and photopeak, but the peak separation is significantly reduced for these longer crystals (see Fig.…”
Section: Resultssupporting
confidence: 74%
“…1) Timing performance: Measuring the 2 × 2 × 3 mm 3 LYSO:Ce:Ca crystals, readout by Broadcom SiPMs, on the ASIC setup results in a CTR of (125 ± 6) ps, which is in accord with the measurements in [32]. The results of BaF 2 show that a photopeak is visible in the energy spectra (see Fig.…”
Section: B Performance Tests For System Applicabilitysupporting
confidence: 74%
“…As with the reported BGO values, these CTRs are consistent with values reported from measurements with high power, high frequency readout chains using the same crystal element size and SiPM. CTR for 20 mm length LYSO:Ce crystals was reported as 132 ± 2 ps in Nadig et al (2022) . In comparison, the test circuit shown in figure 1(a) matched this performance at 5 mW of total power consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, highly integrated front-end designs in the form of ASICs are required. It has been shown that current system-applicable solutions available on the market show a non-negligible contribution of the front-end on the measured CTR [9]. For PET, several ASIC solutions have been developed over the past two decades, amongst others: NINO [10], TOFPET2 [11], STIC [12], and FlexTOT [13].…”
Section: Introductionmentioning
confidence: 99%